Suzuki–Miyaura reactions of 3, 5-dichloro-2, 4, 6-trifluoropyridine. Issue 29 (20th July 2016) - Sharif, Muhammad; Shoaib, Khurram; Ahmed, Shahzad; Iqbal, Jamshed; Abilov, Zharylkasyn A.; Spannenberg, Anke; Langer, Peter
Graphical abstract: Highlights: Simple synthesis of fluorinated pyridines. Mono and double coupling. Suzuki–Miyaura reaction. Abstract: 3, 5-Diaryl-2, 4, 6-trifluoropyridines and 5-aryl-3-chloro-2, 4, 6-trifluoropyridines were prepared through Suzuki–Miyaura reactions of 3, 5-dichloro-2, 4, 6-trifluoropyridine with arylboronic acids in high yields.